The relationship between budget deficit and economic growth from Malaysia’s perspective / Nur Hayati Abd Rahman and Nurul Fahana Aini Harun - Abd Rahman, Nur Hayati; Harun, Nurul Fahana Aini (2012)
Theoretically, there are controversial thoughts that discussed on the relationship between budget deficit and economic growth. While Keynesian economies claimed that these two series are positively related, the neo-classical economies claimed the opposite. Meanwhile, the Ricardian equivalence hypothesis argued that there is neutral relationship between budget deficit and economic growth. The objective of this paper is to investigate the relationship between budget deficit and economic growth from Malaysia’s perspective. Four variables were used, namely real Gross Domestic Product (GDP), government’s debt, productive expenditures and non-productive expenditures. AutoRegressive Distributed Lag (ARDL) approach is used to analyze the long-run relationship between all series since it can cater for small sample size. By using quarterly data from 2000 to 2011, it was found that there is no long-run relationship between budget deficit and economic growth of Malaysia, consistent with the Ricardian equivalence hypothesis. However, productive expenditure has positive long-run relationship with the economic growth. In case if there is a shock in the Malaysian economy, the only variables that can help to converge the economy to its equilibrium is the changes in GDP and productive expenditures. For future recommendation, it is suggested that other researchers will enhance this research by including other developing countries as the sample of analyses.